The Effect of Marketing Mix on Repurchase Intention of Hydroponic Farm Vegetable Products - Abdul Rasyid; Tri Eko Yudiandri; Muhamad Irpan Nurhab; Fioletta Papilaya; D. Yadi Heryadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The goal of this study was to examine how the 7P and 4C marketing mix affected how satisfied consumers were with the vegetable products from Koltivare Hydroponic Farm, to analyze the effect of the 7P and 4C marketing mix on the repurchase intention of Koltivare Hydroponic Farm vegetable products, and to analyze the effect of repurchase intention on the repurchase intention of Koltivare vegetable products. Koltivare Hydroponic Farm and analyzing the marketing mix (7P and 4C) have an effect on repurchase intention, which is mediated through consumer satisfaction with Koltivare Hydroponic Farm vegetable products. Structured equation modeling with partial least squares (SEM-PLS) was the methodology employed in this study, and the SmartPLS 3.0 software was used to run the analysis tools. According to the study's findings, the variables of product, pricing, advertising, people, tangible proof, procedure, and cost directly affect consumer satisfaction. Then there is a direct influence of place, physical evidence, and communication variables on repurchase intention and a direct influence of consumer satisfaction variables on repurchase intention. While the indirect effect shows the results of variables that have an influence on repurchase intention with intervening variables namely product, price, people, and process, the mediation effect of this research is full mediation.